Possibility of large-area carbon nanotube films formation through spray coating - Jinkyeong Kim; TaeGu Lee; Ji-Hoon Han; Joon Hyub Kim (Micro and Nano Systems Letters, 2024)
Abstract This study deals with the process of developing and optimizing the spray coating method for large-area deposition of carbon nanotubes. Carbon nanotubes have excellent electrical and thermal properties and strength, so they are used in various fields of application. However, existing deposition methods have limitations. In this study, the possibility of the spray coating method for large-area deposition of carbon nanotubes is presented, and additional conditions for this are introduced. A spray coating solution was prepared using dichlorobenzene as a solvent for 3 mg carbon nanotubes. By controlling the spray coating speed, the spray coating conditions were optimized by analyzing the surface shape, structure, and resistance of the deposited carbon nanotubes. As a result, we confirmed the possibility of depositing carbon nanotubes on a large area through the spray coating method, and it is expected to contribute to increasing the application possibilities in industrial and scientific fields.